Tracing Paths: Comprehensive Dataset of Online Business and Law Enforcement - Pratama, Sandika; Mediawati, Noor Fatimah; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This study extracted 2,451 documents from Lens.org, filtering for "Online Business" and "Law Enforcement" within "Journal Article" and "Conference Proceeding" types, refined by the subject "Law," aiming to discern the landscape of research in this domain. The comprehensive dataset unveils trends, prominent institutions, active countries, prolific authors, and key publishers in the intersection of online business and law enforcement. The findings offer a rich resource for scholars, students, and researchers, furnishing insights into the field's evolution and serving as a foundational resource for future analyses and literature reviews. Highlights: Comprehensive dataset on online business and law enforcement Reveals trends, institutions, authors, and publishers Valuable resource for scholars and future research Keywords: Online Business, Law Enforcement, Research Dataset, Legal Studies, Trends